2018
DOI: 10.1097/jom.0000000000001167
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well-Being Metrics in Business

Abstract: Pursuit of corporate integrated reporting requires corporate governance and ethical leadership and values that ultimately align with environmental, social, and economic performance. Agreement on metrics that intentionally include HWB may allow for integrated reporting that has the potential to yield significant value for business and society alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Well-being, as it relates to working people, is defined and operationalized in diverse ways 3–6 . As noted by Schulte et al, 7 “…some definitions focus on the state of the individual worker, whereas others focus on working conditions, and some focus on life conditions.” (pe32) In the literature, different indicators of well-being are linked to a host of outcomes of value to individuals, organizations, and society, such as employee retention, financial success, workability, productivity, absenteeism, early retirement, physical and mental health, and happiness, among others 8–14 .…”
mentioning
confidence: 99%
“…Well-being, as it relates to working people, is defined and operationalized in diverse ways 3–6 . As noted by Schulte et al, 7 “…some definitions focus on the state of the individual worker, whereas others focus on working conditions, and some focus on life conditions.” (pe32) In the literature, different indicators of well-being are linked to a host of outcomes of value to individuals, organizations, and society, such as employee retention, financial success, workability, productivity, absenteeism, early retirement, physical and mental health, and happiness, among others 8–14 .…”
mentioning
confidence: 99%
“…As Tsalis et al (2018) found, Evangelinos et al (2018) also discovered very limited disclosure of any OHS target setting and related outcomes. Consistent with these concerns, Pronk et al (2018) argue that there is a case for better integrated reporting of health and well-being metrics that relate corporate programs designed to improve them to evidence of such programs’ impact.…”
Section: Research Into Employee Occupational Health and Safety Initia...mentioning
confidence: 99%
“…As Tsalis et al (2018) found, Evangelinos et al (2018 also discovered very limited disclosure of any OHS target setting and related outcomes. Consistent with these concerns, Pronk et al (2018) argue that there is a case for better integrated reporting of health and well-being metrics that relate corporate programs designed to improve them to evidence of such programs' impact. Montero et al (2009) examined CSR instruments/tools mainly in Europe and found that OHS was mentioned in most cases; however, there was little to suggest that OHS was considered to be anything that went above and beyond the standards required by legislation.…”
Section: Research Into Employee Occupational Health and Safety Initia...mentioning
confidence: 99%
“…As que trataram da mensuração propuseram KPIs para Relatos Integrados que decifrassem a sustentabilidade de uma empresa (Oshika & Saka, 2017) e métricas de saúde e bem-estar para os Relatos Integrados (Pronk et al, 2018). A única pesquisa que abordava a classificação de informações propôs uma codificação para as categorias de risco divulgadas por empresas mineradoras (Moloi, 2015).…”
Section: Informações Relacionadas Ao Processo Contábilunclassified